2013
DOI: 10.1007/s10773-013-1925-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dynamics and Kinematics from a Statistical Model Selected by the Principle of Locality

Abstract: Quantum mechanics predicts correlation between spacelike separated events which is widely argued to violate the principle of Local Causality. By contrast, here we shall show that the Schrödinger equation with Born's statistical interpretation of wave function and uncertainty relation can be derived from a statistical model of microscopic stochastic deviation from classical mechanics which is selected uniquely, up to a free parameter, by the principle of Local Causality. Quantization is thus argued to be physic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 90 publications
(124 reference statements)
0
13
0
Order By: Relevance
“…We have shown in Refs. [19,21] that imposing the principle of Locality of no-influence-at-a-distance singles out uniquely an exponential distribution of deviation from infinitesimal action, up to a free parameter λ which determines its average deviation as |λ/2|. We have also shown that such a statistical model leads to a 'generalized Schrödinger equation' in which the reduced Planck constant of the usual Schrödinger equation is replaced by |λ| (see Eq.…”
Section: Motivationmentioning
confidence: 79%
See 3 more Smart Citations
“…We have shown in Refs. [19,21] that imposing the principle of Locality of no-influence-at-a-distance singles out uniquely an exponential distribution of deviation from infinitesimal action, up to a free parameter λ which determines its average deviation as |λ/2|. We have also shown that such a statistical model leads to a 'generalized Schrödinger equation' in which the reduced Planck constant of the usual Schrödinger equation is replaced by |λ| (see Eq.…”
Section: Motivationmentioning
confidence: 79%
“…To this end, we have argued in Refs. [19,21] that imposing the principle of Locality and Macroscopic Classicality leads uniquely to a class of probability distribution given by the following exponential law:…”
Section: B Exponential Distribution Of Infinitesimal Stationary Actimentioning
confidence: 99%
See 2 more Smart Citations
“…Other predictions, beyond those of quantum mechanics, are being experimentally explored [272,519]. Related developments include two similar models: one based on particles, rather than fields [520], and the other deterministic, rather than stochastic [521]. Not directly related but similar approaches include one based on the interaction of a signal wave with a carrier wave [522], and another based on a retrocausal constraining of a classical field [ [342,[527][528][529][530].…”
Section: Prequantum Classical Theories: a More Descriptive Theory Maymentioning
confidence: 99%